The Diagnosis and Treatment of Sjogren’s Syndrome - Stefanski, A. L.; Tomiak, C.; Pleyer, U.; Dietrich, T.; Burmester, G. R.; Dorner, T. (Dtsch Arztebl Int, 2017)
BACKGROUND: Sjogren’s syndrome is one of the more common inflammatory rheumatological diseases, with a prevalence of at least 0.4% in Germany. METHODS: This review is based on pertinent articles retrieved by a selective search in PubMed. Special attention is drawn to updated classification criteria and current treatment recommendations. RESULTS: Sjogren’s syndrome has a wide variety of presentations, ranging from the local involvement of exocrine glands with keratoconjunctivitis sicca and xerostomia (the leading signs of the disease) to the systemic, extraglandular involvement of multiple organs. Fatigue also markedly worsens the patients’ quality of life. Serologic testing reveals antinuclear auto-antibodies (anti-Ro/ SSA and anti-La/SSB) as well as rheumatoid factors. The histological hallmark of the disease is focal lymphocytic infiltration in otherwise normal-appearing glandular acini. The disease also markedly elevates the risk of non-Hodgkin lymphoma of the B-cell series, which arises in about 5% of patients. Primary Sjogren’s syndrome (pSS) differs from the secondary form (sSS), which appears in the setting of another autoimmune disease, particularly systemic lupus erythematosus (15-36%), rheumatoid arthritis (20-32%), and limited or progressive systemic sclerosis (11-24%). Disease-modifying therapy is reserved for patients with systemic involvement; there is limited evidence for its efficacy. Because of the complexity of this disease, some of its clinical manifestations may require interdisciplinary treatment. CONCLUSION: The main considerations in the interdisciplinary care of patients with Sjogren’s disease are measures to improve quality of life, pharmacological and non-pharmacological treatments to keep disease activity in check, and management of the risk of lymphoma. Future therapeutic approaches must take the heterogeneity of the disease into account.